Immunometabolism in Tuberculosis - Shi, Lanbo; Eugenin, Eliseo A.; Subbian, Selvakumar (Frontiers in Immunology, 2016)
Immunometabolism, the study of the relationship between bioenergetic pathways and specific functions of immune cells, has recently gained increasing appreciation. In response to infection, activation of the host innate and adaptive immune cells is accompanied by a switch in the bioenergetic pathway from oxidative phosphorylation to glycolysis, a metabolic remodeling known as the Warburg effect, which is required for the production of antimicrobial and pro-inflammatory effector molecules. In this review, we summarize the current understanding of the Warburg effect and discuss its association with the expression of host immune responses in tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis (Mtb). We also discuss potential mechanisms underlying the Warburg effect with a focus on the expression and regulation of hypoxia inducible factor 1 alpha (HIF-1), the regulatory subunit of HIF-1, a major transcription regulator involved in cellular stress adaptation processes, including energy metabolism and antimicrobial responses. We also propose a novel hypothesis that Mtb perturbs the Warburg effect of immune cells to facilitate its survival and persistence in the host. A better understanding of the dynamics of metabolic states of immune cells and their specific functions during TB pathogenesis can lead to the development of immunotherapies capable of promoting Mtb clearance and reducing Mtb persistence and the emergence of drug resistant strains.